An ensign to the nations. - The Church of Jesus Christ of Latter-Day Saints (USA The Church of Jesus Christ of Latter-Day Saints, 1997)
Four yeard after the church was organized, the Prophet Joseph Smith met in a small log schoolhouse with priesthood holders in Kirtland, Ohio, and said: Brethen ... you know no more concerning the destinies of this Church and kongdom than a babe upon its mother's lap. You don't comprehend it ... it is only a little handful of Priesthood you see here tonight, but this Church will fill North and South America-it will fill the world (Wilford Eoodruff, in Conference Report, Apr. 1898, 57).
An Ensign to the Nations examines the fulfillment of this miraculous prophecy-the worldwide growth and expansion of The Chrush of Jesus Christ the Latter-Day Saints. Filmed in several countries, this one-hour video-cassette tells of Saints in Europe, the Pacific Islands, Latin America, Asia, and Africa that have helped the kingdom of God to flourish. Their inspiring stories of faith, sacrifice, and perseverance bear witness of the Restoration, showing the influence of gospel pioneers throughout Church history and around the world
Keywords: Church of Jesus Christ the Latter Day Saints